(untitled) (Commonwealth Journal of Local Governance, 2021)
Ghana has pursued decentralisation since 1988, but its implementation continues to face challenges. Participatory monitoring and evaluation (PM&E) is one of the tools that can help local governments to be more effective in the planning and management of development projects. However, the issues involved in implementing PM&E in rural local governments operating within a rapidly changing sociocultural and political environment have not been sufficiently explored. To fill this gap in knowledge, this paper draws on project and policy documents and primary data on the application of PM&E in District Assemblies’ Common Fund projects implemented between 2013 and 2017 in Ghana’s Lambussie District. Six key informant interviews were held with district- and regional-level stakeholders, and eight focus group discussions were undertaken at the community level. The research found that inadequate provision for operationalising PM&E at the local level, and lack of accountability and feedback mechanisms, resulted in a tokenistic approach to PM&E. The authors suggest that research and advocacy on mechanisms for holding district authorities accountable is vital to the success of future PM&E initiatives at local government level.